Answer:
[tex]y=-0.25(x+2)^2+4[/tex]
Step-by-step explanation:
General form of a quadratic function: [tex]y=ax^2+bx+c[/tex]
(where c is the y-intercept)
The y-intercept occurs when x = 0. As one of the ordered pairs is (0, 3) we can say that c = 3
Therefore, [tex]y=ax^2+bx+3[/tex]
Input two ordered pairs into the function and solve simultaneously to find a and b:
Ordered pair (-2, 4):
[tex]a(-2)^2-2b+3=4[/tex]
[tex]\implies 4a-2b=1[/tex]
Ordered pair (1, 1.75):
[tex]a(1)^2+b+3=1.75[/tex]
[tex]\implies a+b=-1.25[/tex]
[tex]\implies a=-1.25-b[/tex]
Substituting second equation into the first and solving for b:
[tex]4(-b-1.25)-2b=1[/tex]
[tex]\implies -6b=6[/tex]
[tex]\implies b = -1[/tex]
Substituting found value for b into second equation and solving for a:
[tex]a=-1.25+1[/tex]
[tex]\implies a=-0.25[/tex]
Therefore, the quadratic function is: [tex]y=-0.25x^2-x+3[/tex]
To complete the square use the formula:
[tex]y=a\left(x+\dfrac{b}{2a}\right)^2+c-\dfrac{b^2}{4a}[/tex]
[tex]\implies y=-0.25\left(x+\dfrac{(-1)}{2(-0.25)}\right)^2+3-\dfrac{(-1)^2}{4(-0.25)}[/tex]
[tex]\implies y=-0.25(x+2)^2+4[/tex]